PEMINANGAN DALAM ISLAM (PERSPEKTIF HADIS NABI SAW) - Darussalam, Andi (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
The purpose of this research is to find out and explain the meaning contained in the hadith about khitbah. This research is a library research consisting of the books of hadith, verses of the Qur’an and supporting data as well as information needed to interpret the data by referring to the explanations of the scholars in the books of hadith, tafseer and so forth. Analysis of the hadith about khitbah is divided into 3 parts: the essence of khitbah, the rules related to khitbah and wisdom (hikmah) from khitbah. This research is expected to contribute ideas or can add information and enrich the treasures of Islamic intellectuals, provide an understanding of the hadith in particular the community about khitbah so that it knows the limits before and after khitbah and this research is useful as a guide in understanding and practice (sunnah) of Rasulullah saw.